(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The purpose of this article is the study of morphonological phenomena in the word formation of the English language of science. Morphonology is a relatively new discipline, and before proceeding to the study of specific material. The authors consider it necessary to acquaint the reader with its main provisions. Morphonology word formation of modern English scientific and technical literature contributes to the standardization of terminological systems based on the mutual influence of the general standard language and the language of science as its functional type. It should be noted that there is no strict dependence between the parameters of word families and modifications of the basis, except for one thing: there is no change of the basis in the adverbial direction of the derivative. Morphological modifications of the producing base in one direction or another, as a rule, are obligatory, but optional. The scientific value is that the wide prevalence of morphological phenomena in the word formation of the English language puts forward the provision on taking into account morphological modifications in the producing basis in the formation of producing words, which is very important in the process of teaching professionally-oriented scientific English. The practical value of this research is that special research in the field of teaching reading literature in the specialty is the main purpose of teaching a foreign language to scientific and technical workers and students of non-linguistic universities. The article concludes that the practice of teaching foreign languages shows that the use of word formation achievements as one of the linguistic disciplines greatly facilitates learning a foreign language. The research uses a comparative method, transformational, descriptive, and semantic. The results of the study indicate the regularity and wide prevalence of morphonological modifications in the generating basis for the formation of derived words in the process of teaching English. Keywords: English language, word formation, scientific and technical vocabulary, morphonology, morphonological phenomena, derivatives; derivation model, a family of words.